The risk to Solanum spp in New Zealand from Gargaphia decoris (Hem Tingidae) a potential biocontrol agent against woolly nightshade S mauritianum - Withers, T.M.; Olckers, T.; Fowler, S.V. (New Zealand Plant Protection, 2002)
Woolly nightshade Solanum mauritianum (Solanaceae) is a serious environmental and forestry weed in New Zealand The leaffeeding lace bug Gargaphia decoris (Tingidae) was released in South Africa in 1999 after rigorous host specificity testing revealed that natives and crops in the genus Solanum were unlikely to be attacked All three New Zealand native Solanum spp were similarly tested in South Africa Neither Solanum laciniatum Solanum aviculare (poroporo) nor Solanum americanum (smallflowered nightshade) supported feeding by nymphs or adults of G decoris in nochoice tests During multichoice tests 97 of adults selected S mauritianum while 2 selected eggplant cv Black Beauty (S melongena) Oviposition occurred only on S mauritianum The risks of nontarget attack are therefore low enough to warrant further evaluation of G decoris as a biocontrol agent in New Zealand